Validity and Reliability Tests of a Love Language Questionnaire in Indonesian - Hikmanisa Bahtiar; Muh Yusuf Liza; Rizka Febrianti; Fasha Nabila Azhari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
The research focuses on the validity and reliability of a love language questionnaire tailored to the Indonesian context, where cultural nuances play a significant role in interpersonal relationships. The sampling technique in this study used a non-probability sampling method to determine the sample tested, where the population was married individuals in the Bone district. Therefore, the technique chosen was the purposive sampling method. Hence, this research consisted of 30 married individuals from the Bone district. A triangulation approach was applied to develop the questionnaire, combining linguistic analysis, psychological insight, and statistical rigor. This method ensured that the questionnaire captured the nuances of love languages in the Indonesian context. The Love Language Questionnaire was grouped into five indicators: acts of service, receiving gifts, quality time, words of affirmation, and physical touch. Each indicator consists of four positive and four negative statements. The type of analysis employed was inferential analysis. The analysis results revealed that 30 items scored above the Pearson correlation coefficient of 0.361, indicating the validity of the items. In addition, Cronbach's alpha coefficients for all indicators exceeded 0.70, indicating reliability. The results indicate that the questionnaire is a valid and reliable instrument for research in psycholinguistics. The limitation wall that hindered the results was the lack of a proper understanding of the sociolinguistic nature of the research population.